2014
DOI: 10.1128/iai.01238-13
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Di-GMP Receptor PlzA Controls Virulence Gene Expression through RpoS in Borrelia burgdorferi

Abstract: bAs an obligate pathogen, the Lyme disease spirochete Borrelia burgdorferi has a streamlined genome that encodes only two twocomponent signal transduction systems, Hk1-Rrp1 and Hk2-Rrp2 (in addition to CheA-CheY systems). The output of Hk1-Rrp1 is the production of the second messenger cyclic di-GMP (c-di-GMP), which is indispensable for B. burgdorferi to survive in the tick vector. The output of Hk2-Rrp2 is the transcriptional activation of the global regulator RpoS, which is essential for the pathogen to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…However, the bosR mRNA level was only moderately reduced, with no statistical significance, in the dhhP mutant (Fig. 8D), suggesting that deletion of dhhP affects BosR mainly at the posttranscriptional level, a phenomenon that has been observed under several other conditions (39,57,66). Thus, DhhP appears to be required for BosR accumulation, which in turn controls production of RpoS and RpoS-dependent virulence factors, including OspC.…”
Section: B Burgdorferi Dhhp (Bb0619) Is a C-di-amp Phosphodiesterasementioning
confidence: 89%
See 1 more Smart Citation
“…However, the bosR mRNA level was only moderately reduced, with no statistical significance, in the dhhP mutant (Fig. 8D), suggesting that deletion of dhhP affects BosR mainly at the posttranscriptional level, a phenomenon that has been observed under several other conditions (39,57,66). Thus, DhhP appears to be required for BosR accumulation, which in turn controls production of RpoS and RpoS-dependent virulence factors, including OspC.…”
Section: B Burgdorferi Dhhp (Bb0619) Is a C-di-amp Phosphodiesterasementioning
confidence: 89%
“…Amazingly, B. burgdorferi accomplishes these dramatic processes with its streamlined genome and limited regulatory repertoire (32). For example, in contrast to many bacteria that have numerous c-di-GMP signaling systems (33)(34)(35)(36), B. burgdorferi has only one c-di-GMP synthase (BB0419, diguanylate cyclase), and it plays an essential role in spirochetal survival in ticks as well as modulating B. burgdorferi motility and mammalian infection (37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…One possibility is that Cu(II) binding of BosR results in conformational changes that render the protein more susceptible to turnover or degradation in vivo. Several studies have indicated that BosR expression is regulated at both transcriptional and posttranscriptional levels (46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Hk2-Rrp2 activates the RpoNRpoS pathway, which is essential for this pathogen to successfully accomplish tick-mouse transmission and establish mammalian infection (11)(12)(13). Recent studies demonstrated that a c-di-GMPbinding protein, PlzA, connects these two signal transduction pathways (14). Environmental stimuli such as temperature, pH, oxygen, carbon dioxide, and undefined mammalian host cell signals have been shown to modulate gene expression in Borrelia (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%